2019
DOI: 10.1038/s41467-019-12359-3
|View full text |Cite|
|
Sign up to set email alerts
|

Possible role of L-form switching in recurrent urinary tract infection

Abstract: Recurrent urinary tract infection (rUTI) is a major medical problem, especially in the elderly and infirm, but the nature of the reservoir of organisms responsible for survival and recolonisation after antibiotic treatment in humans is unclear. Here, we demonstrate the presence of cell-wall deficient (L-form) bacteria in fresh urine from 29 out of 30 older patients with rUTI. In urine, E. coli strains from patient samples readily transition from the walled state to L-form during challenge with a cell wall targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(117 citation statements)
references
References 28 publications
4
104
0
Order By: Relevance
“…Noteworthy, formation of spheroplasts upon G-penicillin treatment has been reported in R. prowazekii (Wisseman et al, 1982), which can be sustained in the organism for a long time and can cause relapse of the infection (Raoult and Roux, 1999;Weissmann, 2005;Sekeyová et al, 2019). The recurrent diseases are generally believed to be caused not by reinfection, but by populations of persister cells, i.e., quiescent forms of bacteria (Fauvart et al, 2011;Brauner et al, 2016;Van den Bergh et al, 2016;Levin-Reisman et al, 2017;Trastoy et al, 2018;Mickiewicz et al, 2019). Most often persisters are represented by cell wall deficient forms (sometimes referred to as L-forms), which are believed to cause relapse of the disease long time after the patients' recovery due to antibiotic administration (Onwuamaegbu et al, 2005;Mickiewicz et al, 2019).…”
Section: Formation Of Persister Cells Upon Treatment With Ampicillin mentioning
confidence: 99%
“…Noteworthy, formation of spheroplasts upon G-penicillin treatment has been reported in R. prowazekii (Wisseman et al, 1982), which can be sustained in the organism for a long time and can cause relapse of the infection (Raoult and Roux, 1999;Weissmann, 2005;Sekeyová et al, 2019). The recurrent diseases are generally believed to be caused not by reinfection, but by populations of persister cells, i.e., quiescent forms of bacteria (Fauvart et al, 2011;Brauner et al, 2016;Van den Bergh et al, 2016;Levin-Reisman et al, 2017;Trastoy et al, 2018;Mickiewicz et al, 2019). Most often persisters are represented by cell wall deficient forms (sometimes referred to as L-forms), which are believed to cause relapse of the disease long time after the patients' recovery due to antibiotic administration (Onwuamaegbu et al, 2005;Mickiewicz et al, 2019).…”
Section: Formation Of Persister Cells Upon Treatment With Ampicillin mentioning
confidence: 99%
“…Pleomorphism and persistence have often been cited as intertwined features in other bacteria, including pathogenic E. coli and Treponema pallidum [313,346]. A recent study provided strong evidence for the role of pleomorphism in urinary tract infection E. coli, in which cell wall-deficient L-forms were reported to confer greater tolerance to penicillin [346]. However, for Lyme Borrelia, the relationship between pleomorphism and antibiotic susceptibility is less established.…”
Section: Pleomorphymentioning
confidence: 99%
“…It has been recently demonstrated that UPEC isolates from elderly patients with rUTI were cell-wall deficient (l-form) bacteria. This feature makes bacteria resistant to cell wall-targeting antibiotics, likely contributing to the recurrence of the infection [19]. Moreover, the increase in antibiotic resistance found in clinical UPEC isolates has made UTI management progressively costlier and more challenging [5,10,18].…”
Section: Introductionmentioning
confidence: 99%